LIPID PEROXIDATION AFTER INTRACORTICAL INJECTION OF FERRIC CHLORIDE INCREASES THE INCIDENCE OF SEIZURES IN YOUNG RATS - Golden, Nyoman; Agus Bagiada, Nyoman; Darmadipura, Sajid (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 3, No. 2 Juli 2009, 2012)
Clinical studies have shown that the incidence of early posttraumatic seizures ishigher in children than in adults and it has been proposed that iron-induced lipidperoxidation has an important role in the development of epileptogenic foci. In this study,we examined some of the hypothesized reasons for the difference in the incidence ofearly posttraumatic seizures between young and adult rats. Twelve young and twelveadult rats were randomized into 4 groups. Group 1 and 2 were control groups, eachcomprising of 6 young rats and 6 adult rats respectively and were given intracorticalinjections of normal saline. Group 3 and 4 were injury groups, again comprising 6 youngrats and 6 adult rats respectively and were given intracortical injections of FeCl3. All ratswere observed for 6 hours post injection for the occurrence of seizures and were thenkilled. The injected hemispheres were extirpated and tested for malondialdehyde (MDA)level and superoxide dismutase (SOD) activity as indices of oxidative damage. Resultsshowed that seizures were observed only in Group 3. Increased MDA level and decreasedSOD activity were observed in Group 3 (ANOVA, p<0.001). Increased MDA levels anddecreased SOD activity were significantly higher in rats with seizures (Group 3) than inthose without seizures (independent t-test, p<0.001). We conclude was that differentlevels of lipid peroxidation induced by intracortical ferric chloride injection may accountfor the different seizure incidence between young and adult rats
Keywords: early posttraumatic seizures, lipid peroxidation, epileptogenic foci, malondialdehyde, superoxide dismutase